1991
DOI: 10.1136/ard.50.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Study of 500 patients with limb joint osteoarthritis. I. Analysis by age, sex, and distribution of symptomatic joint sites.

Abstract: Five hundred subjects with symptomatic limb joint osteoarthritis, who had been referred to a rheumatologist, were enrolled into a continuing study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
142
1
2

Year Published

1996
1996
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(152 citation statements)
references
References 15 publications
7
142
1
2
Order By: Relevance
“…Several epidemiologic studies have shown an association between OA of the hand and OA of the knee in community-based study populations, suggesting that hand OA is often part of a more generalized OA (22)(23)(24). Hand OA has a significant heredity, indicating the presence of a genetic risk factor (13,15).…”
Section: Discussionmentioning
confidence: 99%
“…Several epidemiologic studies have shown an association between OA of the hand and OA of the knee in community-based study populations, suggesting that hand OA is often part of a more generalized OA (22)(23)(24). Hand OA has a significant heredity, indicating the presence of a genetic risk factor (13,15).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown an association between OA of the hand and OA of the knee, suggesting that hand OA is often part of a more generalized OA (Cushnaghan and Dieppe 1991, Hirsch et al 1996. Hand OA has a signifi cant heredity, indicating the presence of a genetic risk factor (Stecher 1941, Spector et al 1996 (Figure 10).…”
Section: Knee Oa After Meniscal Injury Is Not Secondary Oa Onlymentioning
confidence: 99%
“…Studies of cadavers have revealed that full-thickness cartilage defects occur ϳ20 times more often in the knee than in the ankle (2,3). Symptomatic OA with radiographic changes occurs ϳ8-9.4 times more frequently in the knee than in the ankle in patients seeking treatment (4,5). Therefore, several researchers have focused on comparing the cartilages from these 2 joints to determine whether they possess histologic, biochemical, biomechanical, and/or metabolic differences (6)(7)(8)(9)(10).…”
mentioning
confidence: 99%